Field Determination of Phosphate in Environmental Water by Using a Hand-Powered Paper Centrifuge for Preconcentration and Digital Image Colorimetric Sensing - Zhen Pan; Xiaozhan Nong; Yajing Xie; Yan Li; Hui Zeng; Ying Liang; Min Zhang (Journal of Analytical Methods in Chemistry)
Phosphate concentration in natural water has been used as a water quality indicator, as it is one of the major nutrients for aquatic plants. However, the traditional phosphomolybdenum blue (PMB) method has limited sensitivity for visual or camera-based detection, leading to underestimation of the phosphate concentration. We present an ultralow-cost, rapid field preconcentration and digital image colorimetric sensing of low-concentration phosphate method for water analysis. A novel hand-powered paper centrifuge (paperfuge) is used for sample preparation and preconcentration. This paperfuge is made of two circular paper discs and a string. Six centrifuge tubes (CTs) originally used as glue dispensing tips with a sample capacity of ∼230 μL, are loaded on the paperfuge. After sampling, phosphate in the water sample is reacted to form PMB. Then, the reacted sample is drawn into a CT using an autopipette before the CT bottom is sealed by glue. After Oasis® HLB sorbents are added through the top of the CT, the CT top is also sealed with glue. The HLB sorbents adsorb PMB and are accumulated in the CT tip through centrifugation. The CT tips are cut and analyzed with the ImageJ software. It was found that the blue color intensity of sorbents is in a linear relationship to the phosphate concentration, with a linear range of 0–5 μM (r2 = 0.9921) and limit of detection of 0.19 μM. In addition, this method has been applied to in-field water analysis. The results are in agreement with the standard PMB method.